Determining the Impact of Menstrual Cycle on Collegiate Athletes: Self-reported Health Issues, Sports Performance, and Willingness to Discuss Regarding Menstruation - Yetty Septiani Mustar; Bayu Agung Pramono; Febby Alfu Khoirun Nissa; Indra Himawan Susanto; Anna Noordia; Dita Yuliastrid (OVS LLC, 2024)
Background. Gaining a comprehensive understanding of the menstrual cycle, its associated health concerns, and the subsequent effects on athlete performance could facilitate the formulation of educated and tailored strategies for training and participating in competitive sports. In turn, this can decrease the probability of injuries, maintain psychological well-being, and ultimately enhance athlete performance. Objectives. The study aimed to investigate the perspective of collegiate student-athletes related to health issues and sports performance during their menstrual period, both in terms of training and competition, as well as the athletes' willingness to discuss pertaining their menstrual cycle. Materials and methods. Our study included 115 female student-athletes participating in land-based individual/team sports (n = 95) and a combination of land/water-based sports (n = 20). A questionnaire was used to collect data for this cross-sectional study, which was undertaken and completed by the participants. A descriptive analysis was performed, with results  reported in frequency and percentage, followed by the Wilcoxon rank-sum test (Mann-Whitney) to analyze the mean differences between the training participation groups during menstruation. Results. In general, all athletes experienced several health issues, with abdominal pain and lower back pain being the most prevalent. Furthermore, nearly all of them (95.33%) experienced pain on the first day of their periods. Menstruation also influences the performance of female athletes during exercise (70.43%) and competition (73.91%), causing increased fatigue and reduced endurance in the majority of them. Additionally, there is a significant difference between the context of training engagement and the number of weekly exercise sessions (0.011) during the menstrual cycle. Conclusions. Menstruation significantly affects the health and performance of female athletes, both during training and competition. Coaches and athletes must comprehend the menstrual cycle to address this issue effectively. It is crucial that coaches and athletes possess a comprehensive understanding of the menstrual cycle in order to effectively address this issue. Moreover, involving medical professionals and sports nutritionists in managing menstrual cycles is also another strategy for enhancing athlete performance.